2005
DOI: 10.1002/cncr.21193
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous biopsy of pediatric solid tumors

Abstract: The brain has an estrogen‐biosynthetic potential resulting from the presence of neuronal aromatase, which controls the intraneural sex‐steroidal milieu and is involved in brain sexual differentiation, psychobehavioral regulation, and neuroprotection. In the rat brain, three distinct aromatase‐P450‐immunoreactive (AromP450‐I) neural groups have been categorized in terms of their peak expression time (fetal, fetoneonatal, and young‐to‐adult groups), suggesting the presence of region‐specific regulation on brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
2
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 114 publications
4
33
2
9
Order By: Relevance
“…Clinical staging [14][15][16] was as follows: 51 (39.5%) patients were diagnosed with localized disease (stages I-III), 68 (52.7%) were diagnosed with stage IV disease, and 10 (7.8%) patients were diagnosed with stage IVs disease. Follow-up in the 138 patients ranged from 1 to 145 months (median, 62 months).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical staging [14][15][16] was as follows: 51 (39.5%) patients were diagnosed with localized disease (stages I-III), 68 (52.7%) were diagnosed with stage IV disease, and 10 (7.8%) patients were diagnosed with stage IVs disease. Follow-up in the 138 patients ranged from 1 to 145 months (median, 62 months).…”
Section: Methodsmentioning
confidence: 99%
“…Ganglioneuroma was diagnosed in smears containing purely ganglionic cells and schwannian tissue, with reservations because of the small sample. 14 Of the 138 FNA cases, histological analysis also was performed on 63 transcutaneous core needle biopsies 6,15,16 and on 43 surgical specimens, usually after chemotherapy, using the grading system of Shimada et al Aspirated cells were pooled in tubes containing 10 mL of RPMI with ethylenediamine tetraacetic acid and sent to the genomic core facility. Cells were counted on a In samples with > 4 Â 10 6 cells, the excess was cryopreserved for future molecular analyses.…”
Section: 17mentioning
confidence: 99%
See 2 more Smart Citations
“…Another recent report by Soudack et al [3], demonstrated an accuracy of 98% in sonographically guided biopsies of soft tissue tumors. Good results from pediatric patients have also been obtained from core biopsy in a variety of solid tumor types [4]. These reports and others encompass multiple tumor types and patient populations, solidifying the central role of core biopsy for tissue diagnosis.…”
mentioning
confidence: 94%